Significant improvements in the olfactory sensitivity of bipolar I disorder patients during euthymia versus manic episodes: a longitudinal study - Liu, Xianlin; Su, Langjun; Li, Yingying; Yuan, Huiqian; Zhao, Ao; Yang, Chunhong; Chen, Chao; Li, Chunyang (Frontiers in Psychiatry, 2024)
Introduction Research has indicated that individuals diagnosed with bipolar disorder (BD) might experience alterations in their olfaction or levels of serum tumor necrosis factor-α (TNF-α), but no studies have investigated olfactory function and serum TNF-α in BD patients simultaneously. Moreover, there is a lack of existing research that compares the longitudinal olfactory function between individuals with manic and euthymic BD I. Methods Patients with manic BD I (BDM, n=44) and healthy controls (HCs, n=32) were evaluated symptoms (measured via the Young Manic Rating Scale, YRMS), social function (measured via the Global Assessment Function, GAF), serum TNF-α, and olfactory function (via the Sniffin’ Sticks test) including olfactory sensitivity (OS) and olfactory identification (OI). The BDM patients were followed up to the remission period and re-evaluated again. We compared OS, OI and serum TNF-α in manic and euthymic patients with BD I and HCs. We examined the correlation between olfactory function and symptoms, social function, and serum TNF-α in patients with BD I. Results The BDM patients exhibited significantly lower OS and OI compared to the HCs (Z = −2.235, P = 0.025; t = −6.005, P < 0.001), while a positive correlation was observed between OS and GAF score (r = 0.313, P = 0.039). The OS in the BD I remission group (n=25) exhibited significantly superior performance compared to the BDM group (t = −4.056, P < 0.001), and the same as that in the HCs (P = 0.503). The change in OS showed a positive correlation with the decrease in YMRS score (r = 0.445, P = 0.026), and a negative correlation with the course of disease (r = -0.594, P = 0.002). The TNF-α in BD I patients was significantly lower compared to HCs (P < 0.001), and not significantly correlated with olfactory function (all P > 0.05). Conclusion The findings suggest that OS and OI are impaired in BDM patients, and the impaired OS in those patients can be recovered in the remission stage. OI may serve as a potential characteristic marker of BD. OS might be useful as an index for BDM treatment efficacy and prognosis.